Hubungan Dukungan Suami Dengan Tingkat Kejadian Depresi Postpartum Pada Ibu Pasca Melahirkan di RS PKU Muhammadiyah Yogyakarta - Bella Sartika; Dita Kristiana (CV. ITTC INDONESIA, 2025)
THE RELATIONSHIP BETWEEN HUSBAND'S SUPPORT AND THE LEVEL OF POST-BIRTH DEPRESSION AT PKU MUHAMMADIYAH YOGYAKARTA HOSPITAL Bella Sartika¹, Dita Kristiana² ABSTRACT The negative impact of postnatal depression is not only experienced by the mother, but can have an impact on the child and their family as well. Mothers who experience postpartum depression are unable to care for their babies optimally, including being lazy about providing breast milk directly. Husband's support is one of the factors that influences the incidence of postpartum depression. The aim of this research is to determine the relationship between husband's support and the incidence of postpartum depression at PKU Muhammadiyah Hospital Yogyakarta in 2024. The research was conducted from August 2024 to November 2024 at PKU Muhammadiyah Hospital Yogyakarta. The research method employed was descriptive correlational with a cross-sectional design. The research was carried out in August 2024 - November 2024. The population of this study was all postpartum mothers who visited and had an examination at PKU Muhammadiyah Hospital, Yogyakarta. The total population was 136 respondents. The sampling technique was simple random sampling with a total of 58 postpartum mothers. Based on the statistical test output of non-parametric statistical tests using the Chi-square test with SPSS, the Asymp value was obtained. Sig. (2-tailed) 0.03, it can be concluded that Ha is accepted, which means there is a relationship between husband's support and the incidence of postpartum depression in postpartum mothers at PKU Muhammadiyah Yogyakarta Hospital, Ngupasan, Gondomanan District, Yogyakarta City, 2024. After conducting a correlation test, it was found The Pearson Chi-square value is 167, which means there is a relationship between husband's support and low postpartum depression. Husband's support is really needed by mothers in facing childbirth, with support from the people closest to them, mothers are able to get through the difficult times of childbirth, so that the incidence of depression in mothers giving birth can be reduced. Keywords : Husband's Support, Postpartum, Depression ¹Student of Bachelor of Midwifery and Midwifery Professional Education, Universitas Aisyiyah Yogyakarta ²Lecturer of Midwifery and Midwifery Professional Education, Aisyiyah University, Yogyakarta